EVALUATION OF THE FORECAST METHODS OF ELECTRIC ENERGY CONSUMPTION OF THE ENTERPRISES ON THE EXAMPLE OF COAL MINE - Buriy, Sergiy; Khalimov, Volodymyr (Scientific Works of Vinnytsia National Technical University, 2015)
The paper considers the results of the comparison of energy consumption method of the enterprise on coal mine example («Centrosoyuz» State fuel energy company, Lugansk region), carried out, using the electric loads curves, multifactoral regressive models and time series. Main provisions of collection and processing of experimental data and model construction are suggested. Fields of application of the methods, intended for energy consumption forecast are recommended on the base of the research. REFERENCES 1. Эффективное использование электроэнергии и топлива в угольной промышленности / [Волощенко Н. И., Островский Э. П., Мялковский В. И. и др.] ; под ред. Э. П. Островского, Ю. П. Миновского. – М. : Недра, 1990. – 407 с. 2. Руководящий технический материал. Указания по расчету электрических нагрузок: РТМ 36.18.32.4-92: ВНИПИ Тяжпромэлектропроект, 1992. – №6 – 7. – С. 4 – 27. 3. Грядущий Б. А. Баланс электропотребления угольных шахт: Справочное пособие / Грядущий Б. А., Халимов В. В., Стукан Р. Н. – Донецк: ООО «Юго–Восток, ЛТД», 2005. – 250 с. 4 Электрические нагрузки промышленных предприятий / [Волобринский С. Д., Каялов Г. М., Клейн П. Н., Мешель Б. С.]. – Л. : Энергия, 1971. – 264 с. 5. Шидловский А. К. Введение в статистическую динамику систем электроснабжения / А. К. Шидловский, Э. Г. Куренный. – К.: Наукова думка, 1984. – 271 с. 6. Бурый С. В. Разработка метода перспективного планирования электропотребления с применением регрессионных моделей / С. В. Бурый // Кривой Рог. Технические средства и информационные системы, используемые для реализации функций управления. Вестник. – 2013. – № 3. – С. 64 – 68. 7 Сучасні проблеми систем електропостачання промислових та побутових об’єктів : зб. наукю праць за матерыалами Всеукраїнської наук.-техн. конф. викладачів і студентів, 17 – 18 жовт. 2013 р. / відп. ред. О. П. Ковальов. – м. Донецьк «ДВНЗ»ДонНТУ, 2013. – 195 с.